(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Assess the knowledge and attitudes of parents with children under 5 years old regarding fall prevention, and to identify associated factors at Becamex International Hospital. Subjects and methods: A cross-sectional descriptive study was conducted from March to May 2025 at the Pediatric Department and Pediatric Outpatient Clinic of Becamex International Hospital. A convenient sample of 100 parents was surveyed using a validated self-designed questionnaire. Data were analyzed using SPSS version 20. Results: Among participants, 69% had good knowledge about fall prevention, 27% had average knowledge, and 4% had poor knowledge. Regarding attitudes, 61% demonstrated positive attitudes, 38% neutral, and 1% negative. Educational level was significantly associated with both knowledge and attitude (p < 0.001). A moderate positive correlation was found between parental knowledge and attitude (Spearman’s rho = 0.479; p < 0.001). Conclusion: Although most parents showed good knowledge and positive attitudes, a substantial portion still lacked adequate awareness. Educational attainment was identified as the key influencing factor. Strengthening health education and integrating fall prevention content into pediatric care programs is recommended.